Ce post-treatment for increased corrosion resistance of AA2024-T3 anodized in tartaric-sulfuric acid. (1st August 2022) - Prada Ramirez, Oscar Mauricio; Tunes, Matheus Araujo; Mennucci, Marina Martins; Starykevich, Maksim; Neves, Cristina; Ferreira, Mário G.S.; Pogatscher, Stefan; De Melo, Hercílio Gomes
Abstract: The effect of a post-treatment for short time in 50 mM Ce(NO3 )3 solution, with or without H2 O2, on the corrosion of AA2024-T3 anodized in tartaric-sulfuric acid was investigated. Electrochemical (EIS, polarization curves) and corrosion (immersion) tests showed improved performance for samples post-treated at 50 °C in the H2 O2 containing solution. Microstructural characterization (SEM, STEM, GDOES) evidenced the presence of Ce oxyhydroxides both at the surface and within the pores of the anodized layer, and their preferential interaction with defective sites both at micro and nanoscale. Important amounts of Ce-species were found near corrosion products, indicating active corrosion protection by Ce ions. Graphical Abstract: ga1 Highlights: The post-treatment increases the corrosion resistance of the anodic layer. The pores of the anodic layer remain open. The deposition of Ce nanoparticles within the pores of the anodic layer has been demonstrated. Evidences that Ce ions durably remains in the layer hindering corrosion activity.